Simultaneous Determination of Bioactive Xanthone Glycosides and Norlignans from Ethanolic Extract of Anemarrhena asphodeloides by Liquid Chromatography - Islam, M. Nurul; Yoo, Hye Hyun; Lee, Jun; Nam, Joo Won; Seo, Eun Kyoung; Jin, Changbae; Kim, Dong-Hyun (AOAC INT, 2008)
The rhizomes of Anemarrhena asphodeloides Bunge (Liliaceae) are prescribed as crude drugs in herbal medication for the treatment of various diseases such as diabetes, inflammation, and platelet aggregation inhibition. A simple, sensitive, and precise reversed-phase liquid chromatographic method was developed to study the quantitative determination of 5 bioactive compounds from these rhizomes, namely, neomangiferin, mangiferin, isomangiferin, nyasol, and methylnyasol. Chromatographic analysis was performed on Capcell Pak C-18 column (150 x 4.6 mm, 3 mu m) with a mobile phase consisting of acetonitrile, methanol, and 0.1% formic acid at a flow rate of 1.00 mL/min. Quantitation was performed using a UV-visible detector at 260 nm. The method for the determination of reported medicinal agents was accurate and reproducible. Excellent linear behavior was observed over the investigated concentration range of 2.5-100.0 mu g/mL for neomangiferin; 1.5-60.0 mu g/mL for mangiferin; 0.5-20.0 mu g/mL for nyasol; and 0.2-20.0 mu g/mL for methylnyasol; correlation coefficient > 0.99. The intraday and interday precision over the concentration range of compounds was < 6.6% (relative standard deviation) and accuracy was between 94.9 and 109.3%. This method can be successfully applied for the analysis of medicinal compounds from the ethanolic extract of A. asphodeloides Bunge.
Keywords: TANDEM MASS-SPECTROMETRY; SWERTIA-MUSSOTII FRANCH; RAT PLASMA; CAPILLARY-ELECTROPHORESIS; ANTIDIABETIC ACTIVITY; HYPOGLYCEMIC ACTIVITY; ACTIVE CONSTITUENTS; MANGIFERIN; IDENTIFICATION; DIFFERENTIATION